Sistem Pengendalian Salinitas Air Pada Budidaya Cacing Nipah Namalycastis rhodochorde Berbasis Internet of Things (IoT) - Muhammad Soneta Rizkilillah; Ikhwan Ruslianto; Junardi Junardi (JURIKOM (Jurnal Riset Komputer), 2022)
Nypa palm worm (Namalycastis rhodochorde) is a new species of Polychaeta class found in Sei Kakap area. Apart from being obtained from the river coast, cultivation is one way to get worms, but the cultivation of nypa palm worm is still within the scope of the lab and is done manually. Manual cultivation has a problems, especially in controlling water salinity which affects the survival or survival rate of worm. Therefore, this requires an Internet of Things in installation of worm cultivation. This system aims to control the salinity of the water and then monitor the salinity and temperature of the water as well as the temperature and humidity of the air. Another goal is to control water salinity which affects the survival rate of worms. The results of monitoring and controlling the water salinity will be displayed on a website-based application. Arduino Uno is used as hardware that controls the system, NodeMCU ESP32 is used as a tool to connect to the server, water salinity sensor is used to measure water salinity, DS18B20 sensor is used to measure water temperature, as well as DHT11 sensor is used to measure air temperature and humidity. The results of testing the reading system of each sensor obtained an error value 0,017% and 0,032% water salinity sensors, 0,015% DS18B20 sensor, as well as 0.011% and 0.003% DHT11 sensor. Application of the system can reduce water salinity by 1-3 ppt and resulted in the survival rate of worms by 41%.